Os brancos do desassossego: a doutrina das cores segundo José Saramago - Diógenes, Nivaldo Medeiros (2008)
This dissertation presents a study concerning the use of the colors in the Literature. For so much, it is been worth of the analyses of the Portuguese writer's two romances José Saramago: Rehearsal on the Blindness and Rehearsal on the lucidity with the objective of evidencing how the senses are built starting from the new signification of the symbolism of the colors. Based in the theoretical conceptions on the color, a first proposal is had as for the invariable use of the colors in the literature. Finally, it stands out, also, the road to reach the existent speeches inside you crome them.